Acute Effects of Cannabis Concentrate on Motor Control and Speed: Smartphone-Based Mobile Assessment - Hitchcock, Leah N.; Tracy, Brian L.; Bryan, Angela D.; Hutchison, Kent E.; Bidwell, L. Cinnamon (Frontiers in Psychiatry, 2021)
Abstract Background: The use of cannabis concentrate is dramatically rising and sparking major safety concerns. Cannabis concentrate contains tetrahydrocannabinol (THC) potencies up to 90%, yet there has been little research on motor impairment after concentrate use (commonly referred to as “dabbing”). This study measured postural control and motor speed after the use of high potency concentrates in males and females. Methods: Experienced concentrate users (N=65, Female: 46%, 17±11 days/month of concentrate use) were assessed for motor performance in a mobile laboratory before, immediately after, and one hour after ad-libitum cannabis concentrate use. Plasma levels of THC were obtained via venipuncture at each timepoint. We used a remotely deployable motor performance battery to assess arm and leg movement speed, index finger tapping rate, and balance. The sensors on a smart device (iPod Touch) attached to the participant provided quantitative measures of movement. Results: Arm speed slowed immediately after concentrate use and remained impaired after one hour (p<0.001), leg speed slowed one hour after use (p=0.033), and balance decreased immediately after concentrate use (eyes open: p=0.017, eyes closed: p=0.013) but not at one-hour post-use. These effects were not different between sexes and there was no effect of concentrate use on finger tapping speed. Acute changes in THC plasma levels after use of concentrates were minimally correlated with acute changes in balance performance. Conclusions: Use of cannabis concentrates in frequent users impairs movement speed and balance similarly in men and women. The motor impairment is largely uncorrelated with the change in THC plasma levels. These results warrant further refinement of cannabis impairment testing and encourage caution related to use of cannabis concentrates in work and driving settings.